Respuesta :
The answer is: " 11 " .
_______________________________________________________
Note: Rewrite as: " 8 + [ (4 ÷ 2) * 5 ] − 7 " ;
_______________________________________________________
to get: " 8 + [ (2) * 5 ] − 7 " ;
to get: " 8 + 10 − 7 " ;
→ " (8 + 10) − 7 = 18 − 7 = 11 .
The answer is: " 11 " .
___________________________________
_______________________________________________________
Note: Rewrite as: " 8 + [ (4 ÷ 2) * 5 ] − 7 " ;
_______________________________________________________
to get: " 8 + [ (2) * 5 ] − 7 " ;
to get: " 8 + 10 − 7 " ;
→ " (8 + 10) − 7 = 18 − 7 = 11 .
The answer is: " 11 " .
___________________________________